Characteristics and outcomes of participants in colorectal cancer biomarker trials versus a real-world cohort. (3rd April 2021) - Foroughi, Siavash; Wong, Hui-li; Tie, Jeanne; Wong, Rachel; Lee, Margaret; Lee, Belinda; Jones, Ian; Skinner, Iain; Burgess, Antony W.; Gibbs, Peter
Abstract: Background: The restrictive eligibility criteria of therapy-focused cancer clinical trials can limit the external validity of the results. The characteristics and survival outcomes of patients enrolled in stand-alone biomarker studies have yet to be explored. We examined the characteristics of patients enrolled in a series of biomarker studies in stage II and III colorectal cancer (CRC) and of the broader patient population from which the study cohorts were recruited. Material and methods: We examined three distinct trial scenarios: a retrospective cohort study (RCS) where archival tissue samples were analyzed, a prospective observational study (POS) where blood samples were collected but patients received standard treatment and a randomized clinical trial (RCT) where biomarker analysis could inform clinical care. Clinical data for each study time period were extracted from a prospective registry. Results: For all CRC patients ( n  = 4033) in this study, the median age was 70 years and 54% were ECOG 0. For patients in the RCS ( n  = 450), POS ( n  = 284) and RCT ( n  = 230), the median age was 72, 65 and 64 years, with 45%, 74% and 79% being ECOG 0. For the POS and RCT, 33% and 36% of all patients with the relevant disease stage were enrolled over the study recruitment period. Survival outcomes were similar for patients in the RCS and POS. RCT outcome data are not available. Conclusion: As for therapy-based trials, enrollment in prospective biomarker studies may be selective, despite relatively broad eligibility criteria. Characteristics and recruitment were similar for POS and RCT patients, indicating study complexity may not necessarily limit patient recruitment. For the prospective biomarker study cohorts examined, the selective recruitment did not significantly impact survival outcomes, suggesting potential for high external validity.